أثر السنة النبوية فى بناء الحياة السياسية الاسلامية - Mohamad, Ali (Journal of Al-Tamaddun, 2005)
The moulding and understanding Islamic politic are directly related to the teaching of Islam, that is, based on the faith, Islamic kw, and Islctm as a complete way of lift. Islamic politics can been seen as the yardstick for the Muslim’s understanding in all aspects of life, guided by God, and as taught by the Quran and al-Sunnah. Therefore, the influence of al-sunnah and its contibution in understanding Islamic politics can be seen in the activities practice by the prophet Muhammad (PBUH) in every aspects of life of the ummah.